Development of a management guide wheel for cervical cancer - Mahmoud Samy Ismail; Fouad Ismail; Julia Ismail; Muneera AlKhalifa; Rehab Ismael; Reham Fathi; Wassan Al Ani; Shaikha Al Hajri; Nusiba Elhassan; Mooza AlKawari; Aysha AlBinali; Gulmeen Raza; et al. (Annals of Cytology and Pathology - Peertechz Publications, 2022)
We designed and developed a management guide wheel for cervical cancer to facilitate a standard approach and improve the quality of care in managing patients diagnosed with different stages of cervical cancer. Each step of the wheel considers the patient's current medical condition, FIGO stage, and the possible treatment modalities for cervical cancer in her case. We reviewed existing international guidelines on the management of cervical cancer and compared their respective recommendations. This guide wheel is based on recommendations by the following organizations: the National Comprehensive Cancer Network (NCCN), the Society of Gynecologic Oncology (SGO), the European Society of Gynaecological Oncology (ESGO), the European Society for Medical Oncology (ESMO), the American Society of Clinical Oncology (ASCO), the British Gynaecological Cancer Society (BGCS) and the International Federation of Gynecology and Obstetrics (FIGO).